Analisis Mineralogi dan Kimia Dolomit Kabupaten Bone Bolango, Provinsi Gorontalo - Sufriadin Sufriadin; Purwanto Purwanto; Muhammad Rahmatul Jihad; Astina Aras; Angelia Santoso; Miftah Hujannah (Universitas Muslim Indonesia, 2021)
Characterization of dolomite samples from Bone Bolango, Gorontalo Province have been performed with the objective to find out their mineralogical and chemical compositions. Observation and mineral analyses were carried out by means of microscopy and X-ray diffraction methods respectively; whereas chemical composition was determined by using X-ray fluorescence spectrometer. Result of XRD analysis shows that samples contain dolomite [CaMg(CO3)2], calcite [CaCO3] and [SiO2]. The proportion of dolomite is about 60.4% in average and its presence is as replacement of calcite in bioclast components and matrices in the rock. Dolomite crystals are characterized by mosaic texture with euhedral – subhedral in shapes. Spacially, dolomite content increase from west to the east of study area. The XRF analysis reveals that dolomite samples contain MgO ranging between 8.07 and 20.78% while CaO ranges between 30.04 and 56.13%. The SiO2 concentration ranges from 3.50 – 7.55%; whereas Al2O3 ranges from 1.07 – 1.84%. The average MgO content of dolomite about 12.89% can be categorized as calcium dolomite. Dolomite within the study area can be used directly in agriculture sector, but it less suitable as raw materials in glass, ceramic and refractory industries because the average content of MgO is less than 17%. However, it can be increased of their MgO with the application of selective mining or beneficiation process.